P05.26 Efficacy and tolerability of high dose chemotherapy with autologous stem cell rescue after surgery in patients with congenital brain tumors. (19th September 2018) - Guidi, M; Giunti, L; Buccoliero, A; Spacca, B; Lucchesi, M; Farina, S; Fonte, C; Moscheo, C; Censullo, M; Genitori, L; Sardi, I
Abstract: Background: Congenital malignant brain tumors are extremely rare characterized by a poor prognosis. This could be due to a massive size of these tumors when they are diagnosed, the surgical difficulties and the lack of consolidated therapeutic approaches. Being radiotherapy not recommend for very young patients, the most favorable outcome is correlated to the gross total resection. We evaluated genetic characteristics, response rate, progression-free survival (PFS), and overall survival (OS) of high-dose chemotherapy and autologous stem cell transplant (ASCT) after surgery of infants with congenital brain malignancy. Material and Methods: Ten infant aged less than 12 months were included in this study. The median age at diagnosis was 56 days (range: 1–279 days; mean: 80, 9 days). All patients were subjected to a regimen of induction chemotherapy, two high-dose chemotherapy courses and autologous stem cell transplant after surgery. Furthermore, we analyzed the Copy Number Variants (CNVs) profile using SNP/CGH array approach in all patients. We also performed a sequence analysis of the coding regions for investigating the clinical relevance of germline INI1 gene mutation in atypical teratoid/rhabdoid tumors (AT/RT) patients. Results: Pathological diagnosis was available in all cases: 4 anaplastic astrocytomas, 2 glioblastoma multiforme, 2 supratentorial primitive neuroectodermal tumors and 2 AT/RT. In our study only two patients were subjected to maximal surgery. A tumor debulking with macroscopic residual was performed in the other patients. At 1–5 years from diagnosis, the PFS was 80% and 58% and the OS was 90%, 69%, respectively. Two germline INI1 mutations were found in both patients with AT/RT. One patients with AT/RT had a c.618G>A (p.Trp206*) mutation in exon 5 of INI1 gene. The genetic analysis of other patient showed c.175C>T mutation in exon 2 of INI1 in heterozygosis in tumor's DNA. The two patients with AT/RT died early, whereas the other congenital patients showed an 5-years OS of 85%. We found a statistical correlation with OS and PFS with the presence of mutation (p: 0, 0009; p: 0, 01) and the histology (p:0.007 and p:0.0590). Conclusion: Intensive postoperative chemotherapy and ASCT represents the most effective therapeutic approach for congenital brain tumors with a high response rate. The determination of germline INI1 mutation in AT/RT could be a decisive prognostic marker for the palliative choice.